Analysis of the incidence and predictive factors of chronic postoperative pain in adult population - EMRE, İLKİM ECEM (My University, 2018)
Objective: Chronic postoperative pain (CPOP) adversely affects the quality of patients’ livesand cause medical and legal problems and economic loss, due to workforce loss. There is noresearch showing the incidence of CPOP in Turkey. The aim of this study was to find the mostprominent factor in the development of CPOP in patients who underwent any kind of surgicalprocedure.Method: Patients (165 women and 146 men) who were operated on in five hospitals were includedin the study. A patient data sheet and follow-up form were prepared. All patients were followedup for 2 months by telephone calls and asked about their pain scores. When patients reportedpain in 2nd month after their operation, they received re-evaluation and consultation from thepain department.Results: Sixty-seven patients complained of prolonged pain at the site of surgery 2 months aftertheir surgery, and 46 of these patients (14.8%) were diagnosed with CPOP. The presence ofCPOP was statistically significant when patients were grouped in age groups of 18-45 years (A)and older than 45 years (B). A statistically significant relationship was found between CPOPdiagnosis and ASA scores. According to the results, older age (>45 years) and an ASA score of 3play major roles in the development of CPOP.Conclusion: Contrary to previous literature, this study found that factors such as socioeconomic status, type and extent of surgery, geographical region, body mass index, gender,previous experience of pain, drug use and the presence of some neuropathy-related chronicdiseases had no effect on the potential development of CPOP. However, ASA scores and ageplayed major roles in the development of CPOP.

Amaç: Ameliyat Sonrası Kronik Ağrı (ASK) hastaların yaşam kalitesine olumsuz etkilerinin yanı sıra tıbbi ve hukuki sorunlara neden olur ve işgücü kaybı nedeniyle ekonomik kayıpları doğurur. Türkiye’de ASK insidansını gösteren herhangi bir araştırma bulunmamaktadır. Bu çalışmanın amacı, her türlü cerrahi girişimden geçecek olan hastaların ASK gelişiminde en belirgin faktörü bulmaktır. Yöntem: Çalışmaya, beş hastanede ameliyat edilen hastalar (165 kadın, 146 erkek) dahil edilmiştir. Hasta veri kayıt ve takip formu hazırlanmıştır. Tüm hastalar ağrı skorlarının sorulduğu telefon görüşmeleri ile 2 ay takip edilmiştir. İkinci ayda hastalardan ağrısı olduğunu bildirenler, ağrı bölümü tarafından yeniden değerlendirmeye alınmıştır. Bulgular: Altmış yedi olgu, cerrahiden iki ay sonra cerrahi müdahale yapılan bölgede uzun süreli ağrı yakınmasında bulunmuş ve 46 hastada ASK tanısı konulmuştur (% 14,8). Olgular, 18-45 yaş (A) ve 45 yaşından büyük (B) olarak gruplandırıldığında, ASK’ın varlığı istatistiksel olarak anlamlı bulunmuştur. ASK ve ASA skoru arasında istatistiksel olarak anlamlı ilişki belirlenmiştir. Elde edilen sonuçlara göre, 45 yaş üstü ve ASA skoru 3 olan hastalarda ASK oranı daha yüksektir. Sonuç: Literatürün aksine, sosyo-ekonomik durum, ameliyat tipi ve derecesi, coğrafi bölge, vücut kitle indeksi, cinsiyet, ağrı ilaçları, sigara/alkol bağımlılığı ve bazı nöropati ile ilgili kronik hastalıkların varlığı gibi diğer faktörlerin ASK olasılığında etkisi yoktur. Bununla birlikte, ASA ve yaş, ASK olasılığında önemli rol oynamaktadır.
Yetişkin popülasyonda postoperatif kronik ağrı insidansı ve prediktif faktörlerin analizi
Keywords: Genel ve Dahili Tıp